Economic Feasibility of Malaysia and Singapore-Brunei Monetary Reunion: A Scrutiny during Major Financial Crises - Quah, Chee-Heong; Ho, Yew-Joe (Asian Journal of Applied Economics, 2020)
This paper attempts to assess the feasibility of Malaysia to rejoin the monetary union with Singapore and Brunei which it left in 1973. The study scrutinizes particularly the period of two impactful financial crises in the last decades, namely the Asian Financial Crisis in 1997 and the US subprime-caused Global Financial Crisis in 2007-2009. Assessment is made in terms of the real convergence criteria suggested by optimum currency areas (OCA) theory and the nominal convergence criteria specified by the Maastricht Treaty. In light of the endogeneity view of convergence criteria, the relevant features of Malaysia are evaluated against those of Singapore and Brunei to infer the degree of preparedness of Malaysia to access the prevailing Singapore-Brunei monetary union. Results suggest that Malaysia could be as good a candidate as Brunei as a monetary union member with Singapore.